PENDAMPINGAN PELAKSANAAN PENELITIAN TINDAKAN KELAS (PTK) KOLABORATIF UNTUK CALON GURU IPA SMP DI REGION GRESIK - Agung Mulyo Setiawan; Chandra Ayu Pitaloka; Masudatut Toyyibah; Farit Nisaussa'adah (Journal of Social Outreach, 2023)
Based on the observations, it was found that there were several problems experienced by students in schools in the Gresik region, province of East Java, Indonesia. Along with the assignment of professional science teacher candidates at the school, the authors provide a solution assisting the implementation of collaborative classroom action research as a form of community service. This activity was carried out in several junior high schools in the Gresik region in collaboration with local teachers. The objectives of this activity are 1) science teacher candidates could identify student problems and find appropriate learning actions at school, 2) evaluate the progress of science teacher candidates in each cycle, and 3) science teacher candidates could write scientific articles based on the implementation of collaborative classroom action research. With hybrid assisting methods online and offline, this activity can run smoothly and optimally. The results obtained are that PjBL is the most chosen learning model as an action to solve student learning outcomes. Then during the collaborative most chosen, all prospective teachers showed good progress in each cycle. The final result is that professional science teacher candidates can write scientific articles for publication in accredited national journals. Keywords: Teacher Candidates, Science, PTK